Tilt Building (TB) Gun-an Arduino Nano Based Device for Detecting Building Inclination - Sudarmanto, Agus; Poernomo, Joko Budi; Nurjanah, Resa Ahliana (Faculty of Science and Education, UIN Walisongo Semarang, 2024)
The inclination of a building can be a serious issue with potentially fatal consequences if not addressed correctly from the beginning, as it may lead to the building collapsing. Therefore, a tool is needed to detect the tilt of a building to determine the level of inclination. This research aims to design and build the Tilt Building Gun (TB Gun) as a portable device for detecting building inclination that can be easily used anywhere. The research methodology includes the design of hardware, development of software, and overall testing of the device. A miniature building in the form of a laptop-sized box was also constructed. The components used in this research include Arduino Nano, 2 HC-SR04 ultrasonic sensors, and an OLED display. The test results of ultrasonic sensor 1 for horizontal direction yielded an accuracy value of 99.06% and a relative error of 0.94%. Meanwhile, the testing results of ultrasonic sensor 2, with an additional distance of 13.1 cm (distance between ultrasonic sensor 1 and ultrasonic sensor 2 to the ground surface) for vertical direction, resulted in an accuracy of 96.29% and a relative error of 3.71%. Subsequently, testing the building inclination angle with a horizontal distance of 25 cm for ultrasonic sensor 1 and a vertical distance of 20 cm for ultrasonic sensor 2 yielded an accuracy of 98.86% and a relative error of 1.14%. From these accuracy values, it can be concluded that the prototype has excellent accuracy. The building inclination angle data is then displayed on the OLED.